2006
DOI: 10.1007/s11103-006-9049-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maize brown-midrib isogenic lines by cellular UV-microspectrophotometry and comparative transcript profiling

Abstract: The molecular mechanisms underlying cell wall digestibility in maize (Zea mays L.) have been studied in three sets of maize brown-midrib isogenic lines in the genetic background of inbreds 1332 (1332 and 1332 bm3), 5361 (5361 and 5361 bm3), and F2 (F2, F2 bm1, F2 bm2, and F2 bm3). Two complementary approaches, SSH (suppression subtractive hybridization) and microarray-based expression profiling, were used to isolate and identify candidate genes in isogenic lines for bm mutants. Metabolic pathway analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 33 publications
3
43
1
Order By: Relevance
“…In the present study, changes in free phenolic and aromatic proWles, reduced incorporation of phenolic esters and lignin monomers into the cell walls, and the reduced and/or loss of CAD and COMT enzymes speciWc for the lignin biosynthetic pathway were consistent with what has been observed in reduced lignin mutants in sorghum and other plants (Akin et al 1986;Pillonel et al 1991;Bout and Vermerris 2003;Barrière et al 2004;Pedersen et al 2005;Shi et al 2006). Previous studies had indicated that reduction or absence of CAD or COMT activity as a result of brown midrib mutations reduced the total amounts of monolignols synthesized and altered the type of monolignols incorporated into sorghum cell walls (Akin et al 1986;Pillonel et al 1991;Lam et al 1996;HatWeld et al 1999;Bout and Vermerris 2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, changes in free phenolic and aromatic proWles, reduced incorporation of phenolic esters and lignin monomers into the cell walls, and the reduced and/or loss of CAD and COMT enzymes speciWc for the lignin biosynthetic pathway were consistent with what has been observed in reduced lignin mutants in sorghum and other plants (Akin et al 1986;Pillonel et al 1991;Bout and Vermerris 2003;Barrière et al 2004;Pedersen et al 2005;Shi et al 2006). Previous studies had indicated that reduction or absence of CAD or COMT activity as a result of brown midrib mutations reduced the total amounts of monolignols synthesized and altered the type of monolignols incorporated into sorghum cell walls (Akin et al 1986;Pillonel et al 1991;Lam et al 1996;HatWeld et al 1999;Bout and Vermerris 2003).…”
Section: Discussionsupporting
confidence: 89%
“…These results indicate the presence of a locus (loci) unique to either RTx430 or Wheatland that aVects the biosynthesis or incorporation of pCA and FA in the presence of both bmr-6 and bmr-12; similar loci have also been reported in maize (Guillaumie et al 2007). Recent reports with maize suggest that many genes are diVerentially expressed in the diVerent bm plants as compared to WT plants, and the proteins encoded for by these genes are likely to inXuence cell morphology and cell wall composition (Shi et al 2006(Shi et al , 2007. Our data indicate that the unique interactions of the bmr alleles, especially together, with the diVerent sorghum genetic backgrounds are exploitable, and could be utilized to develop sorghum plants with biomass qualities designed to Wt appropriate conversion platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that perturbation of the lignin biosynthetic pathway affects the expression level of other genes on the same pathway (Rohde et al, 2004;Sibout et al, 2005;Shi et al, 2006a;Dauwe et al, 2007;Leplé et al, 2007;Vanholme et al, 2010c). Consequently, feedback and potentially feed-forward regulatory mechanisms must operate.…”
Section: Shikimate Phenylpropanoid and Methyl Donor Pathways Are Timentioning
confidence: 99%
“…Microarray analysis of cad-c cad-d Arabidopsis mutants revealed effects on stress-related pathways and cell wall-related proteins, including lignin, pectin, cellulose, and cell wall-localized proteins (Sibout et al, 2005). Furthermore, a SSH transcript-based comparison of three brown midrib3 (bm3) maize (Zea mays) mutants (mutated in COMT) revealed a feedback on phenylpropanoid and hemicellulose biosynthesis and photosynthesis, and comparisons with bm1 (mutated in CAD) and bm2 (mutated gene unknown) showed a shared response in signaling and regulation (Shi et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing cell wall carbohydrate (principally as cellulose) content in biomass can be expected to increase liquid fuel yield. Decreasing lignin content is also expected to enhance cellulose breakdown, and has been a major target for conventional and molecular breeding [17,18,[87][88][89]104]. However, lowering lignin content could have a negative impact on plant Wtness and survivability of perennial species under Weld conditions [12,70].…”
Section: Introductionmentioning
confidence: 99%